Last Glacial Maximum cryogenic calcite deposits in an alluvial fan at Villetoureix, southwest France. (20th March 2023) - Bertran, Pascal; Couchoud, Isabelle; Charlier, Karine; Hatté, Christine; Lefrais, Yannick; Limondin‐Lozouet, Nicole; Queffelec, Alain
Abstract: The origin of white calcite silts forming 0.5 to 3‐cm‐thick lenses in alluvial fan deposits 14 C‐dated to the Last Glacial Maximum in the Dronne Valley (Dordogne, southwest France) is investigated using microscopic imagery, chemistry, and O and C stable isotopes. The calcite silts, composed mainly of aggregates of 3–5‐μm euhedral crystals, do not resemble secondary precipitations of pedological origin because of the strata‐like pattern and the lack of clearly identifiable biological structures. Their association with evidence of ice formation in the soil (platy structure, involutions) suggests that they were deposited in a deep seasonal frost context. Their isotopic composition differs significantly from those of detrital carbonates and of Holocene bioprecipitation and seems to be best explained by precipitation under closed‐system conditions. Calculation of the isotopic composition of calcite that would have formed in equilibrium with groundwater of regional LGM aquifers provides values that are in the range of the composition of the calcite silts for a precipitation temperature close to 0°C. Therefore, these deposits are interpreted as cryogenic calcite precipitated from waters close to saturation with respect to calcite freezing at the base of/within icings or within the ground, possibly from frost blisters. Similar calcite precipitation at the outlet of karstic springs may have been abundant in the calcareous terrains of southwest France during the LGM, although still unrecognized in the geological record.